Chronic obstructive pulmonary disease exacerbation episodes derived from electronic health record data validated using clinical trial data. Issue 10 (5th August 2019) - Sperrin, Matthew; Webb, David J.; Patel, Pinal; Davis, Kourtney J.; Collier, Susan; Pate, Alexander; Leather, David A.; Pimenta, Jeanne M.
Abstract: Purpose: To validate an algorithm for acute exacerbations of chronic obstructive pulmonary disease (AECOPD) episodes derived in an electronic health record (EHR) database, against AECOPD episodes collected in a randomized clinical trial using an electronic case report form (eCRF). Methods: We analyzed two data sources from the Salford Lung Study in COPD: trial eCRF and the Salford Integrated Record, a linked primary‐secondary routine care EHR database of all patients in Salford. For trial participants, AECOPD episodes reported in eCRF were compared with algorithmically derived moderate/severe AECOPD episodes identified in EHR. Episode characteristics (frequency, duration), sensitivity, and positive predictive value (PPV) were calculated. A match between eCRF and EHR episodes was defined as at least 1‐day overlap. Results: In the primary effectiveness analysis population (n = 2269), 3791 EHR episodes (mean [ SD ] length: 15.1 [3.59] days; range: 14‐54) and 4403 moderate/severe AECOPD eCRF episodes (mean length: 13.8 [16.20] days; range: 1‐372) were identified. eCRF episodes exceeding 28 days were usually broken up into shorter episodes in the EHR. Sensitivity was 63.6% and PPV 71.1%, where concordance was defined as at least 1‐day overlap. Conclusions: The EHR algorithm performance was acceptable, indicating that EHR‐derived AECOPD episodes may provide an efficient, valid method of data collection. Comparing EHR‐derived AECOPD episodes with those collected by eCRF resulted in slightly fewer episodes, and eCRF episodes of extreme lengths were poorly captured in EHR. Analysis of routinely collected EHR data may be reasonable when relative, rather than absolute, rates of AECOPD are relevant for stakeholders' decision making.